Going solo and feeling smart? An exploratory study on shoppers' time valuation and cultural perception - Wang, Xueqin (2023)
Purpose: The advent of digitalization and the trend of social distancing coincide with the individualized lifestyle that is emerging among contemporary shoppers. This study explores the unique market of “smart solo shoppers”. Two empirical studies are conducted, which aim to identify the major dimensions of multi-channel shopping activities that are engaged by the shoppers (Study 1, n = 64) and to differentiate the shoppers' valuation of time invested in the distinct dimensions under different cultural influences (Study 2, n = 519). Design/methodology/approach: A survey questionnaire is used for data collection, and data are analyzed using structural equation modeling. Findings: Results reveal that the shopping activities converge into four principal dimensions: offline shopping, online shopping, post-shopping delivery and product return activities. Shoppers who perceive offline shopping activities as a time burden and online shopping and delivery activities as venues of value creation are more strongly self-identified as smart solo shoppers. Furthermore, smart solo shoppers who are under a strong influence of individualistic culture are found to spend time on multi-channel shopping to make the right purchase the first time, whereas shoppers perceiving being in a weak individualistic culture prefer to engage online channels while being prepared to return the unwanted purchases. Originality/value: This study highlights an emerging research field in the nexus of solo consumption and smart shopping. Emphasizing the utility-driven and ego-expressive nature of smart solo shoppers, the authors provide an initial profile of these shoppers based on their time-valuation patterns and the contextual impacts of individualistic culture.